2020
DOI: 10.3389/fmicb.2020.592592
|View full text |Cite
|
Sign up to set email alerts
|

Swine Manure Composting With Compound Microbial Inoculants: Removal of Antibiotic Resistance Genes and Their Associations With Microbial Community

Abstract: In this study, compound microbial inoculants, including three Bacillus strains and one Yeast strain, were inoculated into swine manure composting to explore the effects on antibiotic resistance genes (ARGs) and mobile genetic elements (MGEs), microbial community structure, and pathogenic bacteria. The results indicated that the abundances of the detected ARGs ranged from 3.6 × 10 3 to 1.13 × 10 8 copies/g. The ARGs with the highest abundance was sul2, and the lowest was blaCTX. Composting removes most of the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…Several of the enriched genes were correlated with int1, which could mean that horizontal transfer was a factor in the enrichment of those genes [82]. This suggests that the microbial compound used has an influence on the type of ARGs that could be removed or enriched [82]. According to current data, one treatment cannot be used to reduce the ARGs of all classes of antibiotics, nor can it be used to completely remove ARGs of a given class.…”
Section: From Pig To Environmentmentioning
confidence: 92%
See 3 more Smart Citations
“…Several of the enriched genes were correlated with int1, which could mean that horizontal transfer was a factor in the enrichment of those genes [82]. This suggests that the microbial compound used has an influence on the type of ARGs that could be removed or enriched [82]. According to current data, one treatment cannot be used to reduce the ARGs of all classes of antibiotics, nor can it be used to completely remove ARGs of a given class.…”
Section: From Pig To Environmentmentioning
confidence: 92%
“…Ectopic fermentation systems were tested and reduced the abundance of tetracycline resistance genes and metal resistance genes in manure [81]. The use of microbial agents during composting can also reduce the number of ARGs and antibiotic residues [75,82]. A study by Liu et al reported that a combination of Phanerochaete chrysosporium, Aspergillus niger, and Bacillus licheniformis was effective in removing oxytetracycline and tetracycline residues, reducing them by 87.8% and 93.7%, respectively, and that P. chrysosporium was more effective for removing doxycycline and enrofloxacin [75].…”
Section: From Pig To Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, their dissipation and persistence still remained unclear, especially the depletion and fate of GAT during the broiler composting process. Most of the studies were based on pig manure composting [ 20 , 21 ], and there was limited understanding of broiler manure composting. This study thus examined the accumulation of six metal elements and the fate and depletion of DOX and GAT during the composting process of broiler manure.…”
Section: Introductionmentioning
confidence: 99%